MCSE training kit microsoft windows 2000 server - Microsoft Corporation (New Delhi Prentice Hall of India, 2001)
Official Microsoft study guide for the skills you need on the job and on the exam. Learn how to set up and support the Windows 2000 Server operating system and prepare for the Microsoft Certificate Programme(MCP)exam
Keywords: Windows (Computer programs); Clint/Server (Computing)